Conceptual Study of Technology-Based Learning Media in Internalizing Religious Ethical Values - Muhammad Irfan Izzuddin; Istanto Istanto (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The increasing moral challenges faced by students in the digital age require educational strategies that are not only cognitively oriented but also capable of fostering a commitment to religious values and ethical behavior. This study aims to formulate a conceptual framework on how technology-based learning media can be designed and implemented pedagogically to internalize religious ethical values in students, by linking the concepts of digital media, value internalization theory, religious character education, and the context of Society 5.0. The method used is a qualitative approach through literature study with content analysis; literature is selected from reputable scientific sources and analyzed thematically to map trends, media forms, success factors, and the potential and challenges of implementation. The results of the study show a shift in the function of technology from merely presenting material to becoming an effective "mediator of valuable experiences" when supported by learning orchestration (assignments, discussions, reflections) so that digital experiences are transformed into ethical meanings. The dominant media discussed include VR/360°, digital game-based learning, interactive multimedia, film-making/docutube, and the e-learning/LMS ecosystem, with the determining factors for success being the alignment of design with value objectives, teachers' pedagogical and digital literacy competencies, and institutional support (infrastructure, training, policies). The main challenges include the risk of reducing values to mere entertainment/visuals, access inequality, and the need for cultural sensitivity and a safe learning space. Conceptually, the internalization of religious ethical values through technology requires value-conscious learning design that is integrated, sustainable, and measurable within the educational ecosystem.